2020
DOI: 10.1111/jace.17362
|View full text |Cite
|
Sign up to set email alerts
|

High‐pressure torsion of SiO2 quartz sand: Phase transformation, optical properties, and significance in geology

Abstract: Phase transformation and optical properties of silica (silicon dioxide, SiO2) quartz sand under high pressure/temperature has been of interest in geology and optical physics for many years. In this study, besides high pressure/temperature, high plastic strain is simultaneously applied to the quartz sand by high‐pressure torsion (HPT) processing. The material shows oxygen vacancy formation and transformation to (a) a denser nanocrystalline quartz phase, (b) a high‐temperature amorphous phase and (c) a high‐pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 79 publications
2
9
0
Order By: Relevance
“…For quartz, there is no phase transition when it is kept in air at 900 or 1000 • C for a long period of time, which is consistent with other reports [21]. However, when it is mixed with potassium silicate glass, as shown in the broken line diagrams in Figures 4, 7, 10 and 11, obvious phase transition occurs: quartz particles first transform into cristobalite, and then into tridymite.…”
Section: The Existence Of Glass Favors Phase Transition Of Quartzsupporting
confidence: 90%
See 1 more Smart Citation
“…For quartz, there is no phase transition when it is kept in air at 900 or 1000 • C for a long period of time, which is consistent with other reports [21]. However, when it is mixed with potassium silicate glass, as shown in the broken line diagrams in Figures 4, 7, 10 and 11, obvious phase transition occurs: quartz particles first transform into cristobalite, and then into tridymite.…”
Section: The Existence Of Glass Favors Phase Transition Of Quartzsupporting
confidence: 90%
“…The schematic illustration of phase transformation of quartz-potassium silicate glass composite is shown in Figure 12. The phase transition of composites will be discussed in the following two aspects: For quartz, there is no phase transition when it is kept in air at 900 or 1000 °C for a long period of time, which is consistent with other reports [21]. However, when it is mixed with potassium silicate glass, as shown in the broken line diagrams in Figures 4, 7, 10 and…”
Section: Phase Transformation Of Quartz-potassium Silicate Glass Compositesupporting
confidence: 88%
“…The inducing ultra-SPD [ 51 ] together with fast dynamic diffusion [ 52 , 53 ] introduces the HPT method as a unique path to mechanically synthesize new materials even from immiscible systems [ 54 , 55 ]. Due to these unique features of HPT, the method was even used for the process and synthesis of hard and brittle ceramics, but the number of publications on ceramics is quite limited despite the high potential of these materials for various applications [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. Published studies regarding ceramics processed or synthesized by HPT are presented in Table 1 , although there are other classic publications on HPT processing of ceramics mainly by physicists and geolog...…”
Section: Influence Of Hpt On Photocatalytic Co 2 C...mentioning
confidence: 99%
“…The formation of high-pressure phases is one of the HPT effects that can occur for some ceramics, such as TiO 2 [ 65 ], ZrO 2 [ 58 ], ZnO [ 26 ], SiO 2 [ 34 ], VO 2 [ 78 ], Y 2 O 3 [ 66 ], BaTiO 3 [ 64 ], Al 2 O 3 [ 27 ], and BN [ 68 ]. It was observed that these high-pressure phases contain defects, such as oxygen vacancies and dislocations, and have nanosized grains, which makes them attractive for photocatalytic applications.…”
Section: Influence Of Hpt On Photocatalytic Co 2 C...mentioning
confidence: 99%
See 1 more Smart Citation